Formation of architecture of new business centers in the project of Astana city - Syzdykov, Нурбек (Рroblems of engineering and professional education, 2023)
The article discusses the actual problems of the formation of modern trends in business centers on the example of the city of Astana. The rapidly growing city of Astana has already formed its own style in urban planning. This is very noticeable in the construction of business centers.